Evaluating Properties of Asphalt Mixtures Containing polymers of Styrene Butadiene Rubber (SBR) and recycled Polyethylene Terephthalate (rPET) against Failures Caused by Rutting, Moisture and Fatigue (Fracture and Structural Integrity, 2020)
Properties of asphalt mixture play a vital role in structural integrity and performance of flexible pavements structure. In flexible pavements asphalt concrete surface layer consists of asphalt binder, aggregates and in some cased additives.In this research study styrene butadiene rubber (SBR) and recycled polyethylene terephthalate (rPET) used to evacuate their individual and also their combination effects upon moisture susceptibly, rutting and low temperature cracking of asphalt concrete mixture.Three combination of SBR and rPET along with water were vulcanized to from thermoplastic elastomer polymers as bitumen modifier. Then conventional bitumen tests including penetration grade, softening point and rotational viscosity (RV) as well as asphalt mixture tests including resilient modulus, dynamic creep, IDT fatigue and moisture susceptibility tests were performed on binders and asphalt mixture specimens. The test results indicated that SBR and rPET increase viscosity and softening point and stiffen the binders by reducing their penetration grade. Test results of spearmens prepared with modified binders showed higher tensile strength and higher rutting resistance than that of control specimen within the contest of this study it is conclude that modification of bitumen with SBR reduces low temperature stiffness of binder and hence reduces failure of thermal cracking and modification with rPET increases rutting resistance of the mixture at high temperatures.
Keywords: SBR; rPET; Resilient modulus; Dynamic creep; Moisture susceptibility; Fatigue test